A big data-driven eHealth approach to prevent, detect, and reduce atherosclerotic cardiovascular disease burden. (11th May 2022) - Scheenstra, B; Bruninx, A; Van Daalen, F; Stahl, N; Latuapon, E; Townend, D; Bermejo, I; Dekker, A; Spreeuwenberg, M; Maessen, J; Van 'T Hof, A; Kietselaer, B
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Netherlands Organisation for Scientific Research (NWO) eHealth is a promising tool to support citizens and patients to reduce their risk of future atherosclerotic vascular disease (ASCVD). Currently, many eHealth initiatives are developed, however their use is limited. To improve the adoption of eHealth initiatives, personalization is needed according to preferences and understanding of the individual. Together with stakeholders, we used the design thinking method to create a dream user-scenario for an eHealth solution to improve cardiovascular outcomes. This point-of-view shows the essential concepts of such an eHealth initiative and focuses on scientific solutions and the most important challenges faced during its development. In the user-scenario a federated data infrastructure collects distributed medical and non-medical data from different organizations, while ensuring maximal privacy. This data, that is currently not available, is used in a screening model to identify citizens with an increased risk for ASCVD. Citizens at risk are offered the use of an eCoach, which is connected to a counterfactual prediction model to calculate a residual risk for hypothetical interventions. This risk is visualized in a personalized way to support the shared decision making process of personalized lifestyle and healthcare goals. eHealth modules, integrated in the eCoach, encourages the patient in achieving these goals. Relevant outcomes are monitored and are used to adjust the intensity of the modules and follow-up accordingly. To realize this federated data infrastructure, an ethical and legal framework should be developed to ensue responsible data handling.